Risk factor of severe preeclampsia in Dr. Soetomo Hospital Surabaya in 2015 - Amelia Rahmah Kartika; Muhammad Ilham Aldika Akbar; Pirlina Umiastuti (Majalah Obstetri dan Ginekologi, 2017)
Objectives: to determine which of the risk factors above associated with the occurrence of severe preeclampsia at dr. Soetomo Hospital, Surabaya during 2015.Materials and Methods: The type and design of the study were analytic and retrospective. This study was held in the dr. Soetomo Hospital from April until November 2016. The instrument of the study was the medical records then being coded and analysed. The samples were 134 pregnant women, consisting of 67 pregnant women with severe preeclampsia as cases and 67 pregnant women as controls.Results: Maternal obesity (OR= 5,786; 95% CI: 2,300–14,555), history of hypertension (OR= 6,693; 95% CI: 1,848–24,237) and secondary elderly primi (OR= 6,384; 95% CI: 1,357–30,031) are associated with the development of severe preeclampsia.Conclusion: In conclusion, the significant risk factors of severe preeclampsia in dr. Soetomo Hospital Surabaya during 2015 are obesity, history of hypertension and secondary elderly primi variables.